Transition prediction in transonic turbine configurations using a correlation-based transport equation model. (1st January 2011) - Benyahia*, Abdelkader; Houdeville, Robert
The Menter correlation-based transition model has been implemented in the CFD code elsA. The model is a framework for taking into account laminar/turbulent transition effects into CFD simulations. The model has been evaluated on two-transonic turbine configurations experimented at the Von Karman Institute. The first case is the well-known 2D Nozzle Guide Vane LS89; the second test case is the CT3 stator/rotor configuration on which quasi 3D computations have been accomplished. Results obtained with the Menter transition model pointed out real improvements in terms of heat transfer predictions. The laminar zones and the transition onset are well-captured and the early transition situated on the rotor leading edge for the CT3 case is also well-produced.